E-maintenance platform: a business process modelling approach (2014)
The information and communications technologies (ICT) are increasingly used in society and business. ICT have become a key element for business development and the improvement of activities in all departments. Analogously, the rise of Computerized Maintenance Management Systems (CMMS), Condition Based Maintenance (CBM), and the use of remote devices and functions such as e-maintenance, have opened great possibilities for maintenance optimization. Those techniques have resulted in the emergence of technological challenges such as interoperability between different systems in order to exchange and coordinate information. In this context, the application of business process modelling is a crucial methodology to understand and implement those maintenance techniques. In this paper, we use business process modelling approach to design a system architecture that integrates CMMS, CBM and e-maintenance methods, tools, and processes. The data model is based on the MIMOSA standard.